Work-Life Balance: A Case Study of a Working Woman in Delhi - Kumar , Rajesh; Agrawal, Vinita (International Journal of Psychosocial Rehabilitation, 2020)
Work-life balance is an important issue of consideration in corporate, especially for women who find it difficult to balance between the two equally demanding and pressing work areas. This research paper explores the life of a woman working in a reputed textile manufacturing company in Delhi in the form of a case study. The paper explores the transition that takes place in her professional life after marriage. It also shows her approach to the challenging career before marriage. Her professional downfall occurs because of the building social responsibilities that come with marriage.